A short history of ethics : a history of moral philosophy from the homeric age to the twentieth century - Maclntyre, Alasdair (Routledge, 1998)
A Short History of Ethics has over the past thirty years become a key philosophical contribution to studies on morality and ethics. Alasdair MacIntyre writes a new preface for this second edition which looks at the book 'thirty years on' and considers its impact. A Short History of Ethics guides the reader through the history of moral philosophy from the Greeks to contemporary times. MacIntyre emphasises the importance of a historical context to moral concepts and ideas showing the relevance of philosophical queries on moral concepts and the importance of a historical account of ethics. A Short History of Ethics is an important contribution written by one of the most important living philosophers. Ideal for all philosophy students interested in ethics and morality.